Adherence to augmentation therapy for the treatment of major depressive disorder. (16th March 2023) - Forma, Felicia; Liberman, Joshua N.; Rui, Pinyao; Ruetsch, Charles
ABSTRACT: Background: Inadequate response to antidepressant medication is common. Often, adjunctive pharmacotherapy or psychotherapy is recommended. Objective: To measure adherence to adjunctive pharmacotherapy and psychotherapy among individuals with major depressive disorder (MDD). Methods: Retrospective cohort study of individuals with MDD on antidepressant monotherapy who added adjunctive pharmacotherapy and/or psychotherapy. Medication adherence was measured by proportion of days covered (PDC) with optimal adherence defined as PDC≥0.80 and psychotherapy adherence defined by count of visits (optimal 8+ visits). Factors associated with optimal adherence were assessed by logistic regression. Results: Among 218, 192 individuals with adjunctive therapy, 185, 349 added pharmacotherapy and 32, 843 added psychotherapy. In the subsequent 12 months, 36.2% and 54.9% achieved optimal adherence to adjunctive pharmacotherapy and psychotherapy, respectively. Adherence to adjunctive pharmacotherapy was associated with adding psychotherapy, index antidepressant adherence, medical comorbidities, and MDD severity codes. Adherence to adjunctive psychotherapy was associated with adding another medication, previous psychiatry visit and psychiatric comorbidities. Conclusion: Adjunctive psychotherapy appears under-utilized and adherence to adjunctive therapy was low. Low adherence to adjunctive therapy reinforces challenges in managing MDD. That a second adjunctive therapy enhanced adherence to the initial adjunctive therapy indicates an opportunity to explore alternative adjunctive therapies.